The role of macrophages in the formation of hypertrophic scars and keloids - Xu, Xiangwen (Burns Trauma, 2020)
Numerous studies have shown that macrophages can orchestrate the microenvironment from the early stage of wound healing to the later stages of scar formation. However, few reviews have highlighted the significance of macrophages during the formation of abnormal scars. The purpose of this review was to outline the polarization of macrophages from early to late stage of pathological scar formation, focusing on spatiotemporal diversity of M1 and M2 macrophages. In this review, the role of macrophages in the formation of hypertrophic scars and keloids is summarized in detail. First, an increased number of M2 cells observed before injuries are significantly associated with susceptibility to abnormal scar pathogenesis. Second, decreased expression of M1 at the early stage and delayed expression of M2 at the late stage results in pathological scar formation. Third, M2 cells are highly expressed at both the margin and the superficial region, which is consistent with the invasive property of keloids. Finally, this review helps to characterize strategies for the prediction and prevention of pathological scar formation.